When a Short-term Analysis is not a Short-term Approach: Impacts of Agricultural Technology Adoption in Bolivia - Julián Aramburu; Mario González Flores; Lina Salazar; Paul Winters (Inter-American Development Bank (IDB), 2014)
This paper presents the results of an impact evaluation for the CRIAR program, implemented in rural areas in Bolivia. The objective of this program is to increase the agricultural income and food security of smallholder farmers through productivity gains that result from technological adoption. We use data obtained from a sample of 1,287 households-817 beneficiaries and 470 controls- interviewed specifically for this evaluation, and rely on a methodology of Propensity Score Matching. Overall, the main impacts of the program are observed in short- and medium-term variables, including crop diversification, input use and expenditures, and variables related to sales and home consumption. For the medium-term variables, the program had a positive impact on sales at the farm gate, market sales, agricultural income from sales, and a decrease in the proportion of production allocated for home consumption. The program also had a significant and positive impact on the food security of beneficiary households. For the long-term indicators, the analysis did not identify significant impacts on productivity variables. The lack of productivity impacts is probably due to the short period after program implementation, which corresponds to only one agricultural cycle. This length of time may have not been sufficient for farmers to gain experience and knowledge with regards to their effective use of the newly acquired technologies or to adjust the production process through input changes.
hdl:11319/6676
Keywords: O13; O33; Q12; Q18; 330; Technology Adoption; Food Security; Productivity; Propensity Score Matching; Bolivia